Millennial Workers in Ride-Hailing Start-Ups: Preferences, Work-Life Balance, and Retention - Raisa Hillia Aini Syifa; Ari Arisman; Heny Hendrayati; Mochamad Achyarsyah; Herdiyanti Herdiyanti; Mahardi Mahardi; Krisztina Taralik; Hayatuk Safrah Salleh (Universitas Pendidikan Indonesia, 2025)
Millennial workers, as the majority of the workforce in Indonesia, possess unique characteristics such as quick adaptation to technology, a preference for work flexibility, and a high need for work- life balance. However, they also have weaknesses, such as high mobility, dependency on technology, and vulnerability to stress due to high expectations. This study aims to analyze the characteristics of millennial workers in start-up companies, particularly in the ride-hailing sector. A survey method was employed, involving 404 respondents from Go-Jek, Grab, and Maxim. The data were analyzed descriptively to describe demographics, educational levels, tenure, and work preferences. The results show that millennial workers prioritize flexibility, innovation, and technology but tend to have short tenures. These findings provide recommendations for companies to adopt management strategies based on technology, flexibility, and approaches that support employee engagement to enhance retention and productivity.